K.H. Ahmad Sanusi (1888-1950): Biografi Ulama Hadis Keturunan Nabi saw Asal Sukabumi - H. Istikhori (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
Hadith scholars are individuals who play an important role in the spread of the Prophetic traditions. in the midst of his people, as an authoritative source after the Qur'an for the complete Islamic legal construct, which was previously discovered and compiled by the Imam of Hadith (mukharrijūn) in their canonical books, like Imam Muḥammad ibn Ismā’īl al-Bukhārī (d. 256 H) in “Ṣaḥīḥ al-Bukhārī” and Muslim Imam ibn al-Ḥajjāj al-Naysābūrī (d. 261 H) in “Muslim Ṣaḥīḥ”, through long tracing from one country to another in order to obtain directly one history from the source. The position of the Hadith scholars in this regard, who are at the spearhead of the spread of the Hadiths after their collection by the Imam of the Hadith, as well as their existence and consistency in guarding the Hadith from various forms of deviation of understanding of the people, become an integral part of an integral circle named Hadith, as a saying of the Prophet, the Rabbis and the Imams.